A facile route to fabricate thermally conductive and electrically insulating polymer composites with 3D interconnected graphene at an ultralow filler loading. Issue 32 (6th August 2019) - Song, Shiqiang; Wang, Jinyuan; Liu, Cheng; Wang, Jincheng; Zhang, Yong
Abstract : A facile route has been developed to prepare highly thermally conductive composites including silicone, styrene–butadiene rubber and epoxy resin matrices. Abstract : Thermally conductive polymer composites show attractive prospects as thermal management materials in many applications such as microelectronic devices. However, traditional approaches in the preparation of thermally conductive polymer composites usually have the disadvantages of complex processes. In this study, a facile method for highly thermally conductive silicone rubber composites is reported, based on 3D interconnected graphene sponges by using an inorganic salt as a sacrificial template. The composites exhibit a high thermal conductivity of 1.50 W m −1 k −1 and a thermal conductivity enhancement of 752% at a very low graphene loading of 1.46 wt%. More significantly, highly thermally conductive epoxy and styrene–butadiene rubber composites are also fabricated by the same method. The composites also show excellent electrical insulating properties (>10 13 Ω cm). Thus, this effective method is proved to be widely used for the facile fabrication of polymer composites of both plastic and rubber matrices which are thermally conductive and have excellent electrical insulating properties.